Landing for success: a biomechanical and perceptual analysis of on-ice jumps in figure skating - Lockwood, K. L.; Gervais, P. J.; Mccreary, D. R. (Sports Biomechanics, 2006)
Technical evaluation in the sport of figure skating is characterized by a subjective marking system. Figure skating judges are responsible for quickly and accurately discerning the quality of technical elements as well as assigning a score to the overall aesthetic appearance of a performance. Traditionally, overall placement marks are assigned for the entire performance; however, the landing of a jump is widely acknowledged as one of the most critical elements of a skater's program. Therefore, our aims were to identify the biomechanical variables that contribute to technical success in executing landings and to establish whether landings rated as biomechanically optimal are also awarded high technical merit scores by judges. Ten nationally ranked competitive figure skaters were asked to execute on-ice, double and triple revolution jumps and to try to land the jumps void of technical faults within a calibrated space. Data were collected at 60 Hz using standard three-dimensional videography. Data reduction was done using the APAS system (Ariel Dynamics Inc). Concurrently, videotapes were viewed and evaluated by 42 accredited judges to determine the perceived technical quality of the landing performances. Judges were asked to evaluate the landing phase of each jump against a landing criteria document. A comparative criteria model was developed to facilitate an assessment of excellence in landing performances through both empirical and subjective analyses. Results of these analyses were twofold: a biomechanical profile of on-ice landings was obtained, and on-ice jump landing strategies rated by empirical evaluations were in agreement with judge's perceptions of the same performances. Im Eiskunstlaufen erfolgt die Bewertung und damit die Klassierung der Sportler anhand der Benotung der Gesamtleistung, dabei ist jedoch zu beachten, dass die Landung eines Sprungs einer der kritischsten Punkte in den Programmen von Eiskunstläufern darstellt. Daher war es Ziel der Untersuchungen, die biomechanischen Variablen zu erkennen, die für den technischen Erfolg einer Landung zuständig sind und festzustellen, ob als biomechanisch optimale Landungen ebenfalls hohe Bewertungen durch die Kampfrichter erhielten. Zehn Eiskunstläufer führten auf dem Eis Doppel- und Dreifachsprünge aus und versuchten eine fehlerfreie Landung in einem kalibrierten Bereich. Mittels 3-D-Videoaufzeichnung wurden die Daten der Sprünge erfasst (Datenreduzierung mittels APAS). Die Videos wurden anschließend von 42 akkreditierten Kampfrichtern betrachtet um anhand eines Kriterienkatalogs die technische Qualität der Landungen zu beurteilen. Es wurde ein vergleichendes Kriterienmodell für die Bewertung der Ausführungsqualität der Landung sowohl durch empirische als auch durch subjektive Analyse entwickelt. Die Analysen erbrachten zwei Ergebnisse:Einerseits erhielt man ein biomechanisches Profil von Landungen auf dem Eis, zum Anderen standen die empirischen Bewertungen von Landungen von Sprüngen auf dem Eis in Einklang mit den Wahrnehmungen der Kampfrichter.